The Physical Quality of Milled Rice as Affected by Moisture Content and Relative Humidity during Delayed Rough Rice Drying - Tamrin Tamrin; Filli Pratama; Bagus Septian (Turkish Journal of Agriculture: Food Science and Technology)
Delayed rough rice drying was often found in tidal low land in Indonesia due to rice harvesting used to be in rainy season. Moisture re-absorption of rough rice during delayed drying caused fissures and breakage after rice milling. This experimental works condition the rough rice in some different moisture content and relative humidity during delayed drying. This aim of this study was to develop an alternative condition of delayed rough rice for drying so as not to significantly affect the physical quality of milled rice. The experiment was arranged as a factorial-randomized block design. Each treatment was repeated three times. Rough rice of IR42 variety was selected at three level of moisture content (24.89%, 18% and 22%), and was stored in a closed vessel at the relative humidity of 76% and 86%. The percentage of whole grain, head rice, large broken grain, and small broken grain were daily assessed until 7 days of delayed drying duration. The results showed that the moisture content and relative humidity had a significant effect on all parameters on each day of delayed rough rice drying duration. Rough rice would be better delayed for drying at the conditions for moisture content of 22% and relative humidity of 86%.